Plastron osteotomy in the management of fishing hook ingestion in a Malayan box turtle (Cuora amboinensis) - Che' Amat, Azlan; Saw, Ming Hooi; R., Noorshimah; Cheah, E. H. C.; Lam, J. L.; Norsidin, Mohd Jefri (Veterinary Association Malaysia, 2015)
An adult male Malayan box turtle was diagnosed with foreign body obstruction of fishing hook. Upon presentation, the animal had pale mucous membrane and fishing line protruding out from the oral cavity. Diagnosis of foreign body ingestion was based on plain radiograph where the fishing hook was evidenced on the lateral and ventrodorsal radiographic view. Plastron osteotomy surgical removal was performed after endoscopy guided forcep removal failed. Procedures were carried out under the injectable anesthesia using a combination of ketamine and xylazine hydrochloride. Antibiotic, anti-inflammatory and parenteral fluid therapy was given pre and post-surgically as medical treatment and stabilisation.